Telemedical cardiac risk assessment by implantable cardiac monitors in patients after myocardial infarction with autonomic dysfunction (SMART-MI-DZHK9): a prospective investigator-initiated, randomised, multicentre, open-label, diagnostic trial. Issue 2 (February 2022) - Bauer, Axel; Sappler, Nikolay; von Stülpnagel, Lukas; Klemm, Mathias; Schreinlechner, Michael; Wenner, Felix; Schier, Johannes; Al Tawil, Amani; Dolejsi, Theresa; Krasniqi, Aresa; Eiffener, Elodie; Bongarth, Christa; et al.
Summary: Background: Cardiac autonomic dysfunction after myocardial infarction identifies patients at high risk despite only moderately reduced left ventricular ejection fraction. We aimed to show that telemedical monitoring with implantable cardiac monitors in these patients can improve early detection of subclinical but prognostically relevant arrhythmic events. Methods: We did a prospective investigator-initiated, randomised, multicentre, open-label, diagnostic trial at 33 centres in Germany and Austria. Survivors of acute myocardial infarction with left ventricular ejection fraction of 36–50% had biosignal analysis for assessment of cardiac autonomic function. Patients with abnormal periodic repolarisation dynamics (≥5·75 deg 2 ) or abnormal deceleration capacity (≤2·5 ms) were randomly assigned (1:1) to telemedical monitoring with implantable cardiac monitors or conventional follow-up. Primary endpoint was time to detection of serious arrhythmic events defined by atrial fibrillation 6 min or longer, atrioventricular block class IIb or higher and fast non-sustained (>187 beats per min; ≥40 beats) or sustained ventricular tachycardia or fibrillation. This study is registered with ClinicalTrials.gov, NCT02594488 . Findings: Between May 12, 2016, and July 20, 2020, 1305 individuals were screened and 400 patients at high risk were randomly assigned (median age 64 years [IQR 57–73]); left ventricular ejection fraction 45% [40–48]) to telemedical monitoring with implantable cardiac monitors (implantable cardiac monitor group; n=201) or conventional follow-up (control group; n=199). During median follow-up of 21 months, serious arrhythmic events were detected in 60 (30%) patients of the implantable cardiac monitor group and 12 (6%) patients of the control group (hazard ratio 6·33 [IQR 3·40–11·78]; p<0·001). An improved detection rate by implantable cardiac monitors was observed for all types of serious arrhythmic events: atrial fibrillation 6 min or longer (47 [23%] patients vs 11 [6%] patients; p<0·001), atrioventricular block class IIb or higher (14 [7%] vs 0; p<0·001) and ventricular tachycardia or ventricular fibrillation (nine [4%] patients vs two [1%] patients; p=0·054). Interpretation: In patients at high risk after myocardial infarction and cardiac autonomic dysfunction but only moderately reduced left ventricular ejection fraction, telemedical monitoring with implantable cardiac monitors was highly effective in early detection of subclinical, prognostically relevant serious arrhythmic events. Funding: German Centre for Cardiovascular Research (DZHK) and Medtronic Bakken Research Center.